ON A BOUNDARY VALUE PROBLEM FOR A TIME-FRACTIONAL WAVE EQUATION WITH THE WEIGHTED RIEMANN-LIOUVILLE AND ATANGANA-BALEANU DERIVATIVES (Scientific journal of the Fergana State University, 2023)
In the article a boundary value problem has been formulated and studied for a wave equation involving Riemann-Liuville and Atangana-Baleanu fractional operators with weight functions. The problem was investigated using the Fourier method. In this case, a solution of the problem with respect to the time variable was found using the Laplace transform. The solution to the problem has been represented by series.